Managing Botrytis blossom blight of wild blueberry through field sanitation, lime sulfur and Trichoderma application. Issue 3 (4th May 2022) - Abbey, Joel A.; Percival, David; Anku, Kenneth; Schilder, Annemiek; Asiedu, Samuel K.
Abstract: Botrytis blossom blight is an important disease of wild blueberries ( Vaccinium angustifolium ) and causes substantial yield loss annually. Field trials that involve primary inoculum reduction and disease reduction techniques were conducted for the 2015/2016 and 2019/2020 growing seasons. The aim of this study was to evaluate the single and combined effects of thermal treatment, calcium polysulphide and Trichoderma harzianum T-22 application on Botrytis blossom blight development, physical plant structure and harvestable yield over the 2-year production cycle of the crop. The treatments were such that fields were thermally treated in May after pruning, followed by calcium polysulphide application in November 2015 and 2019. Trichoderma harzianum was applied in June 2016 and 2020 as single and combined treatments. Thermal treatment + calcium polysulphide + T. harzianum and thermal treatment + calcium polysulphide combinations reduced Botrytis blossom blight incidence and severity by over 50% and 74%, respectively, compared with the untreated control in both seasons. Plots receiving only the thermal treatment and calcium polysulphide as well as the calcium polysulphide + T. harzianum combination showed reductions in disease incidence of over 51, 38 and 81%, and reductions in disease severity of 55, 39 and 68%, respectively, compared with the untreated control. Plots that received thermal treatment combined with calcium polysulphide had taller stems, and a higher number of floral and vegetative buds. Results from this study have demonstrated that Botrytis blossom blight in wild blueberry fields can be adequately reduced when calcium polysulphide is used tandem with thermal treatment and biofungicides.